2009
DOI: 10.1111/j.1440-1746.2009.05801.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation dynamics and platelet functions in obstructive jaundiced patients

Abstract: Even though there is a general assumption about the increased bleeding tendency in obstructive jaundiced patients, we could not demonstrate reduced clotting activity by measuring with either PFA or TEG. On the contrary we observed tendency for hypercoagulation independent of increased prothrombin times. The most probable cause of this effect is the increased activity of fibrin polymers on platelet membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…26 Kawle et al found that serum levels of NSE were an independent predictor of the outcome in IS patients. [29][30][31] Thus, high levels of NSE and bilirubin indicate severe brain injury and a poor prognosis, while patients with low-NSE concentrations might have a better neurological recovery. 28 Bilirubin is an important antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…26 Kawle et al found that serum levels of NSE were an independent predictor of the outcome in IS patients. [29][30][31] Thus, high levels of NSE and bilirubin indicate severe brain injury and a poor prognosis, while patients with low-NSE concentrations might have a better neurological recovery. 28 Bilirubin is an important antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K deficiency can cause prolongation of prothrombin time (PT) and activated partial thromboplastin time (aPTT), but other screening tests typically remain normal. 9 Even so, a study by Çakır et al 11 evaluated standard measures of coagulation as well as thromboelastography and platelet function using PFA-100 before and after relief of obstruction in 23 patients with obstructive jaundice mainly due to underlying malignancy. Although PT was prolonged in 56% of patients, this was not associated with an increase in bleeding risk as assessed by these functional assays.…”
Section: Preoperative Considerations Obstructive Jaundicementioning
confidence: 99%
“…For instance, hypercoagulation has been detected among patients with obstructive jaundice. The authors reported a correlation between strength, elasticity and coagulation indices of the clot and increased concentrations of direct bilirubin [ 17 ]. Other studies also report a significant positive correlation between high bilirubin concentration and prolonged APTT and PT times, basic markers of coagulation efficacy [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%